(untitled) (Research, Society and Development, 2022)
Introduction: In dentistry, several studies tend to show that breastfeeding on demand, especially at night and lasting more than 6 months, causes caries. The American Academy of Pediatric Dentistry (AAPD) pronounces itself pointing to breast milk as a risk factor for the first dentition due to the occurrence of caries and bottle feeding, especially for children who follow prolonged and repetitive feeding without following appropriate oral cleaning measures. , with the absence of a precise definition, the use of the term weaning, some dentists advise parents to stop offering milk to children before 1 year of age, thus discouraging extended breastfeeding and on demand. Objective: to analyze myths and truths about caries in infants who are exclusively breastfed. Methodology: Narrative review carried out through the VHL, including articles from 2011 to 2021, containing the keywords: breastfeeding, caries, infants. Results: Several studies indicate that caries is one of the most common infectious diseases among children, and it is estimated that, in Brazil, it has a superiority five times greater than that of asthma and seven times greater than that of allergic rhinitis. Despite this, breastfeeding is recommended from 6 months to the first 2 years of life. Final Considerations: Current studies have demonstrated the cariogenicity of several foods given to children and the non-cariogenicity of breast milk. Therefore, we must guide parents towards safe and caries-free breastfeeding.